2021
DOI: 10.1249/mss.0000000000002805
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Flow Restriction Training on Blood Perfusion and Work Ability of Muscles in Elite Para-alpine Skiers

Abstract: Purpose The effects of short-term blood flow restriction (BFR) exercise on muscle blood flow perfusion and performance during high-intensity exercise were determined in elite para-alpine standing skiers to assess whether this would be an effective training regimen for elite athletes with disabilities. Methods Nine national-level para-alpine standing skiers (mean age, 20.67 ± 1.34 yr; four women) were recruited. Nondominant lower limbs were trained with BFR (eight in fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Similarly, it was reported that two weeks of BFR training (×2/day, 6 days/wk) at 20% of 1RM improved the squat 1RM in young individuals ( Abe et al, 2005 ), which concurs with the results of the present study. In support of the above, a recent study by Geng et al (2022) reported improved muscle strength in national-level para-alpine standing skiers after two weeks of resistance training combined with BFR. Although the exact molecular mechanisms driving the hypertrophic adaptations following LL-BFR are unknown at present, a recent study by Davids and colleagues (2021) showed that this form of resistance training enhanced muscular responses without the need for high mechanical loads likely through stimulating similar cellular and molecular pathways to HL-RT.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, it was reported that two weeks of BFR training (×2/day, 6 days/wk) at 20% of 1RM improved the squat 1RM in young individuals ( Abe et al, 2005 ), which concurs with the results of the present study. In support of the above, a recent study by Geng et al (2022) reported improved muscle strength in national-level para-alpine standing skiers after two weeks of resistance training combined with BFR. Although the exact molecular mechanisms driving the hypertrophic adaptations following LL-BFR are unknown at present, a recent study by Davids and colleagues (2021) showed that this form of resistance training enhanced muscular responses without the need for high mechanical loads likely through stimulating similar cellular and molecular pathways to HL-RT.…”
Section: Discussionmentioning
confidence: 54%
“…From a practical standpoint, BFR-RT could be a beneficial supplemental training protocol for trained population. It has been demonstrated that the combination of BFR- and HL-RT was more beneficial for the increase of muscle strength [ 97 ]. Thus, healthy individuals or athletes are likely to maximize their training adaptations by combining these two training methods [ 4 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a practical standpoint, BFR-RT could be a bene cial supplemental training protocol for trained population. It has been demonstrated that the combination of BFR-and HL-RT was more bene cial for the increase of muscle strength [97]. Thus, healthy individuals or athletes are likely to maximize their training adaptations by combining these two training methods [4,98].…”
Section: Discussionmentioning
confidence: 99%